REPRESENTASI KEKERASAN KULTURAL PADA WANITA DALAM FILM SI DOEL THE MOVIE 2 - Anissa Meiriam Swastinastiti; Sunarto Sunarto; Lintang Ratri Rahmiaji (Interaksi Online, 2023)
Films are a product of human thought, making films effective mass media because it can be explained that film themes are very important in media semiotics. The form of violence against women that is often applied in Indonesia is an important social discourse because understanding violence in films can always influence society. The film Si Doel The Movie 2, which is taken from Aman's novel, was chosen as the research subject because the narrative depicts a character who is culturally oppressed because she is a woman and has the status of a wife. This study uses a critical paradigm to critically dismantle the meanings and ideas contained in film texts. Using a qualitative approach and Roland Barthes’ semiotic research method, the researcher wants to know how the film text of Si Doel The Movie 2 represents cultural violence against women that appears through the audio and visual aspects of the film. The selected lexia is analyzed through two meanings, which are denotative (literal) and connotative. The author applies data collection techniques in the form of observation and documentation to analyze the text in the film Si Doel The Movie 2. The theory used is Stuart Hall's representation theory and Simone De Beaviour's Feminist Existentialism Theory. The results of this research are that the film Si Doel The Movie 2 presents a false representation of cultural violence, there are several indicators regarding signs that refer to the existence of feminism itself, namely women's equality, so that this film strengthens and justifies the shackles of women based on violence that occurs continuously. cultural events such as fear, intolerance and satire where the dominance of masculine elements is seen in this film and this is a motif of patriarchal ideology which is reflected in scenes in the film that erode equality